An optical system for noninvasive microscopy of psoriatic mice in vivo. Issue 4 (2nd January 2023) - Lu, Yiting; Zhu, Yujie; Zhao, Xiaohui; Pan, Meng; He, Hao
Abstract: Psoriasis is a chronic inflammatory skin disease involved with both complex morphological changes of skin and immune processes. The clinical diagnostics and research of psoriasis often require invasive biopsy which lacks their real‐time dynamics in vivo. Here we report a noninvasive microscopic system developed by combining in vivo fluorescent microscopy, optical clearing, and immunolabeling to enable real‐time imaging of immune cells and cytokines in blood flow in psoriatic animal models. The vascular morphology and time‐lapse kinetics of interleukin (IL)‐23, IL‐17, tumor necrosis factor‐α, and CD4+ cells in blood are captured at submicron resolution through the thickening epidermis and opaque scales during the development of psoriasis in vivo. Our data suggest IL‐23 recruits CD4+ cells to release IL‐17 in blood that further leaks out in the psoriatic skin area. This optical system enables noninvasive and real‐time assessment of immune molecules and cells in vivo, providing good potential for medical researches on psoriasis. Abstract : We developed a noninvasive microscopy scheme by combining in vivo fluorescent microscopy, optical clearing, and immune‐labeling to enable real‐time imaging of immune cells and cytokines in blood flow in psoriatic animal models through the thick opaque scales and inflammations. The vascular morphology and time‐lapse kinetics of interleukin (IL)‐23, IL‐17, tumor necrosis factor‐α, and CD4+ cells in blood are captured at submicron resolution through the thickening epidermis along the development of psoriasis in vivo.